Le rôle de l’université verte dans le développement d’infrastructures respectueuses de l’environnement, conformément aux critères de classement mondial pour soutenir les objectifs de développement durable- référence à l’université de Wageningen, classée numéro un dans le monde- - Ala Eddine Louafi (OpenEdition, 2020)
This study aims to highlight the effective role of universities in the development of environmentally friendly infrastructure in accordance with the criteria of the global classification to support the Sustainable Development Goals, and which has reached a sustainable and long-term development of society aimed at meeting the needs of humanity now and in the future through rational use, the renewal of natural resources, the preservation of land for future generations, as well as sustainable development aimed to eradicate poverty in all its forms everywhere, to eradicate hunger, to achieve food security, to improve nutrition and promote sustainable agriculture, as well as ensure a healthy life and promote well-being for all at all ages... The areas of great interest to the University of Wageningen for sustainability are energy, construction, sustainable procurement, waste, food and mobility. Finally, the study has recommended the need to take care of universities due to their active role in achieving the sustainable development goals, as well as the need to benefit from the expertise of universities, which rank first in the world ranking of universities in order to achieve sustainability.